Seniority Reconstruction and Violence Prevention in Pesantren: A Hybrid Model of Power Transformation - Syamsul Arifin; Mufiqur Rahman; Muhammad Abri Harahap; Imam Tazali; Hamidullah Marazi (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2026)
Violence and bullying in Indonesian Islamic boarding schools (pesantren) are rooted in seniority hierarchies through which senior students exercise supervisory authority over juniors. Existing scholarship either defends this hierarchy as pedagogically necessary or calls for its abolition. Neither position addresses reconstruction: how the tradition might be reshaped rather than preserved or dismantled. This study used an interpretive, embedded single-case design to examine how Ma'had Baitul Qur'an Madura transforms senior–junior power relations to prevent violence. Data were collected over six months (July–December 2025) through in-depth interviews with 13 purposively selected participants (senior students, junior students, ustadz, and administrators), participant observation, and document analysis. Analysis drew on a combined Foucault–Weber–Bourdieu framework to trace simultaneous shifts in power modality, authority legitimacy, and dispositional foundations. The institution operationalized a hybrid model retaining the structural position of seniority while reorienting its operative logic from coercive discipline to moral and spiritual exemplarity through five integrated mechanisms: faith-based compliance, moral-leadership redefinition, prophetic pedagogical capacity, home–pesantren alignment, and cross-hierarchical solidarity. Administrators delivered these through an integrated curriculum, leadership formation (daurah), teacher capacity building, parental engagement, and solidarity programming (Ukhuwah Week). Disciplinary records documented a 65.95% reduction in recorded violations across implementation phases (Semester 1: n = 213; Semester 2: n = 64), with coercive incidents declining 43.48%. A pesantren can pursue violence prevention without dismantling its defining traditions. The hybrid model offers a configurational, transferable framework for administrators and policymakers pursuing child-friendly Islamic education, applicable where kiai-centered authority and multi-domain programming capacity are present